2018
DOI: 10.21467/ajgr.5.1.8-15
|View full text |Cite
|
Sign up to set email alerts
|

SiC Particulate Reinforced Aluminium Metal Matrix Composite

Abstract: Al or Al alloy Metal Matrix Composites have wide range of applications i.e. aerospace, automobile etc. due to its lightweight, high tensile strength, high wear resistance. This review paper characterized the SiC particulate reinforced Al Metal Matrix Composites. The SiC particulates are dispersed in Al or Al alloy by liquid state processing route and solid-state processing route. Stir casting liquid processing route has been followed by no. of researchers due to its simplicity and low processing cost and at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 23 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The silicon carbide particles are randomly dispersed in a Ti6Al4V(ELI) matrix to create a composite. The SiC particles are ceramics and are stiffer and more bri le than Ti6Al4V(ELI) which is a ductile material [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The silicon carbide particles are randomly dispersed in a Ti6Al4V(ELI) matrix to create a composite. The SiC particles are ceramics and are stiffer and more bri le than Ti6Al4V(ELI) which is a ductile material [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…% of ceramic particulates content. Murlidhar Patel et al [19] in their study, made efforts to develop an Al composite reinforced with SiC by using liquid stircasting technique. It was observed that, composites mechanical behavior improved by the adding of SiC.…”
Section: Introductionmentioning
confidence: 99%
“…This problem leads to an easy crash of material on the application of high load. It may be controlled by incorporating particulate materials like SiC, B4C, etc., into the aluminium alloy matrix [5,6]. However, SiC/B4C as reinforcement material creates additional problems of depletion of the aluminium oxide layer formed on the composite surface.…”
Section: Introductionmentioning
confidence: 99%